1979
DOI: 10.1111/j.1751-1097.1979.tb07055.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF ULTRAVIOLET IRRADIATION ON EGGS AND LARVAE OF THE NORTHERN ANCHOVY, ENGRAULIS MORDAX, AND THE PACIFIC MACKEREL, SCOMBER JAPONlCUS, DURING THE EMBRYONIC STAGE*

Abstract: Abstract— Anchovy and mackerel eggs and yolk‐sac larvae were exposed to UV radiation in the bioactive band of wavelengths between 280 and 320 nm. the UV‐B region of the spectrum. Irradiation levels were based upon predicted UV‐B increases that would result from anthropogenic diminution of Earth's protective ozone shell. Dose‐response relationships for mortality and histological and morphological effects were determined for two different spectral energy compositions, using FS‐40 sunlamps and two filter combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 6 publications
1
81
2
Order By: Relevance
“…On the contrary, the RAFs associated with the 2 DNA action spectra (Setlow 1974, Hunter 1979 as well as all RAFs determined for other DNA-related effects (Madronich 1993) were much greater than our estimate. BWF are a function of the absorption spectra of the target molecule and the negative impact of the energy absorbed onto the process studied (e.g.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…On the contrary, the RAFs associated with the 2 DNA action spectra (Setlow 1974, Hunter 1979 as well as all RAFs determined for other DNA-related effects (Madronich 1993) were much greater than our estimate. BWF are a function of the absorption spectra of the target molecule and the negative impact of the energy absorbed onto the process studied (e.g.…”
Section: Discussioncontrasting
confidence: 53%
“…1992); (c) diatom (Phaedactylum sp.) and (d) dinoflagellate (Prorocentrum micans); (e) DNA damage in anchovy eggs and larvae (Hunter 1979, redrawn from Smith & Baker 1982; and ( f ) the naked DNA damage as onginally described by Setlow (1974) allow for enhancement of primary production by the longest wavelengths of UVR, expressed as: Quantifying how sensitive the determination of the BWF was to a change in the inhibition input parame-ters FITnm required a realistic estimate of the error around FIT,, as well as a Tvay to quantify the assoclated change in the BWF. We chose the RAF as an estimator of the general shape of the BWF As described above, the residuals from the linear fit used to determine FIT,,, represented -10% of the signal.…”
Section: Bwf and Raf For Antarctic Phytoplanktonmentioning
confidence: 99%
“…While the migration is energetically expensive, lowering reproductive output, it is more adaptive than remaining in dangerous sunlit surface waters (DeMeester and Beenaerts, 1993;Duncan et al, 1993). In stark contrast to this paradigm, dispersing larvae of many decapod crustaceans and fishes are abundant near the sea surface in the daytime (e.g., Hunter et al, 1979;Morgan and Christy, 1996). Although this phenomenon has been documented many times, its direct contradiction to the prevailing paradigm has not received much attention from ecological and evolutionary biologists.…”
Section: Introductionmentioning
confidence: 93%
“…The work of Marinaro & Bernard (1966), Pommeranz (1974) and Hunter et al (1979Hunter et al ( , 1981Hunter et al ( , 1982 provided clear evidence of the detrimental effect of UV-B on the planktonic early life, stages of marine fishes. Hunter et al (1979), working with northern anchovy Engraulis mordax and Pacific mackerel Scomber japonicus embryos and larvae, reported that exposure to surface levels of UV-B could be lethal. Significant sublethal effects were also reported: lesions in the brain and retina, and reduced growth rate.…”
Section: Ecological Context Direct Effects Of W Radiationmentioning
confidence: 99%